Associations between Types and Sources of Dietary Carbohydrates and Cardiovascular Disease Risk in 110, 505 UK Biobank Study Participants. (14th June 2022) - Kelly, Rebecca; Tong, Tammy; Watling, Cody; Reynolds, Andrew; Perez-Cornago, Aurora; Carter, Jennifer; Key, Timothy; Piernas, Carmen; Papier, Keren; Schmidt, Julie
Abstract: Objectives: Recent studies have reported that the associations between dietary carbohydrates and cardiovascular disease (CVD) may depend on the quality, rather than the quantity, of carbohydrates consumed. This study aimed to assess the associations between types and sources of dietary carbohydrates and CVD risk. Methods: We used data from 110, 505 UK Biobank participants with ≥2 (maximum of 5) 24-hour dietary assessments who were free from CVD and diabetes at baseline. Multivariable Cox regressions were used to estimate risks of incident (non-fatal and fatal) total CVD, ischemic heart disease (IHD) and stroke, by carbohydrate intakes, including total carbohydrates, carbohydrates from refined grains, carbohydrates from wholegrains, total sugars, free sugars, non-free sugars, and fiber. Models were adjusted for sociodemographic, lifestyle, and anthropometric factors, including body mass index. We also estimated the associations between modelled isoenergetic substitution of 5% of energy from carbohydrates from refined grains with wholegrains and 5% of energy from free sugars with non-free sugars. Results reported below survived false discovery rate correction for multiple testing. Results: Over a median 9.4 years of follow-up, there were 4, 188, 3, 138, and 1, 124 cases of total CVD, IHD and stroke, respectively. While total carbohydrate intake was not associated with CVD risks, free sugar intake was positively associated with total CVD (HR; 95% CI per 5% of energy, 1.07; 1.04–1.10), IHD (1.06; 1.02–1.10), and stroke (1.11; 1.04–1.18), although associations were non-significant for IHD in analyses by fourths of intake. Fiber intake was inversely associated with total CVD (HR; 95% CI per 5 g/day, 0.95; 0.91–0.98) and IHD (0.94; 0.91–0.98). Modelled isoenergetic substitution of 5% of energy from carbohydrates from refined grains with wholegrains was inversely associated with total CVD (0.95; 0.92–0.98) and IHD (0.94; 0.91–0.98), and substitution of free sugars with non-free sugars was inversely associated with total CVD (0.95; 0.92–0.98) and stroke (0.91; 0.86–0.97). Conclusions: Higher free sugar intake was associated with higher CVD risks. Higher fiber intake and replacement of refined grains and free sugars with wholegrains and non-free sugars, respectively, were associated with lower CVD risks. Funding Sources: This work was supported by the Clarendon Fund.